Combination of Hardware and Software Security Mechanisms for Embedded Systems with Internet of Things - J S Prasath (AI Society & STMIK Indonesia, 2026)
Embedded systems are fast growing technologies and it is widely used in varieties of applications. Embedded devices are susceptible to variety of attacks due to its large number of deployment, resource limitations and increased complexity. Intruders try to acquire the process information from the embedded devices through variety of security attacks. It is essential to protect the embedded system along with wireless networks from unauthorized access and modification of process parameters. The novelty of this proposed work is the implementation of hybrid security algorithm along with the exclusive hardware key using embedded system which performs secure transmission and monitoring of process variables over internet. This proposed hybrid security algorithm is a mixture of asymmetric, symmetric and hash function algorithms which assures strong security. The process data security is strengthened by generating large key size of 2048-bit in this proposed asymmetric encryption and 256-bit key size for symmetric encryption. It also encrypts the hardware key along with the hybrid encryption. The encryption algorithm is performed at the master node and the decryption algorithm is performed at the two slave nodes. When the master node fails due to some fault, then one of the slave node acts as master and sends the encrypted data to another slave node. The slave node acts as redundant node as well as it performs hybrid decryption. The hardware key is essential to access and modify the encryption code as well as to monitor the cipher text both at the transmitter and the receiver. This proposed security algorithm is cost effective and it prevents the sensitive process information from illegal access and alteration.